Analisis Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Sistem Informasi Akuntansi, Sistem Pengendalian Internal Dan Peran Audit Internal Terhadap Kualitas Laporan Keuangan - Free Antonius Simanjuntak (CV. Ulil Albab Corp, 2023)
This research is conducted to analyze the impact of Human Resource Competence, Usage of Accounting Information System, Internal Control and The Role of Internal Audit on the Quality of Financial Statement in, which happens from September 2023 to December 2023. The research methodology that we used in this research is survey methodology. The instrument we used is quesionnaire to collect data for human resource competence, the usage of Accounting Information System, Internal Control and The Role of Internal Audit on the Quality of Financial Statement. The research results show that according to our analysis, it is known that employee of possess fairly good human resource competence, good usage of accounting infomation system, good internal control and audit internal